2019 Novel Coronavirus Vaccination among Post-graduate Residents and Fellows. (May 2021) - Abohelwa, Mostafa; Elmassry, Mohamed; Abdelmalek, John; Payne, Drew; Nugent, Kenneth
Background: Coronavirus-2 (COVID-19) has caused a worldwide pandemic since December 2019. Since then, clinical trials with vaccines have been started and completed, and at present, 3 COVID-19 vaccines have been approved for use in the United States. Healthcare providers were among the first to get vaccinated, but the precise attitudes of healthcare workers toward vaccination are uncertain. Objective: To understand residents and fellows' attitudes toward vaccination and record any side effects after vaccination. Methods: We conducted an anonymous survey that was open from 3-1-2021 to 3-12-2021 using distribution lists from the Graduate Medical Education office on the Lubbock campus of the Texas Tech University Health Sciences Center after getting approval from the Institutional Review Board (L21-088). Results: Eighty-one residents and fellows (26.6% out of 304) responded to our survey. Among those who responded, 63 (77.8 %) were between 25 and 35 years old, and 41 (50.6%) were males. Seventy-seven (95.1%) received the vaccine (Pfizer-BioNTech), 78 (96.3%) reported that they supported vaccination, and 3 (3.7%) reported that they did not want vaccination. Eight members (9.8%) had tested positive for COVID-19 infection before vaccination, but only 1 (1.23%) had tested positive for COVID-19 antibodies. All residents and fellows reported side effects after the vaccination, including pain at the injection site (77; 100%), local redness (9; 11.6%), local swelling (13; 16.8%), fever (25; 32.5%), fatigue (25; 32.5%), chills (34; 44.1 %), headache (38; 49.4%). Conclusions: Most medical trainees have a high interest in COVID-19 vaccination; however, a few reported that they did not want vaccination.